Relationship between Employee Pre-Retirement Adjustment Styles and Knowledge Sharing Intentions in State Corporation in Kenya. - kembu, Appolonius Shitiabai; Amuhaya, Iravo Mike; Guyo, Wario (IJRDO - Journal of Applied Management Science, 2016)
Knowledge management of the aging workforce is a major challenge, particularly to state corporations in Kenya. Psychological effects of disengagement from a work life and the transition to retirement may influence knowledge sharing intensions. The objective of the study was to examine the relationship between employee pre-retirement Adjustment styles and knowledge sharing intentions in state corporations in Kenya listed in the Kenya Gazette. The study used exploratory design. The population of the study comprised of all 202 State Corporations in Kenya. The study used purposive sampling to obtain data from the population through a questionnaire. The study targeted employees who were within retirement age. Quantitative data was collected to enable the researcher conduct an in-depth study. The study carried out a pilot test to test the validity and reliability of the questionnaires in gathering the data required for purposes of the study. Simple linear regression and multiple regression analyses was used to establish the nature and magnitude of the relationship between variables and to test hypothesized relationships. The study established that employee pre-retirement adjustment styles had greater effect on knowledge sharing intentions. The study also established that preretirement anxiety enhanced knowledge sharing intentions in State Corporations in Kenya. It further found that the relationship was stronger where State Corporations were based in the same sector and weaker when they were across Sectors. These research findings contribute by